Physical mechanisms of earthquake nucleation and foreshocks: Cascade triggering, aseismic slip, or fluid flows? - Zhigang Peng; Xinglin Lei (Earthquake Research Advances)
Earthquakes are caused by the rapid slip along seismogenic faults. Whether large or small, there is inevitably a certain nucleation process involved before the dynamic rupture. At the same time, significant foreshock activity has been observed before some but not all large earthquakes. Understanding the nucleation process and foreshocks of earthquakes, especially large damaging ones, is crucial for accurate earthquake prediction and seismic hazard mitigation. The physical mechanism of earthquake nucleation and foreshock generation is still in debate. While the earthquake nucleation process is present in laboratory experiments and numerical simulations, it is difficult to observe such a process directly in the field. In addition, it is currently impossible to effectively distinguish foreshocks from ordinary earthquake sequences. In this article, we first summarize foreshock observations in the last decades and attempt to classify them into different types based on their temporal behaviors. Next, we present different mechanisms for earthquake nucleation and foreshocks that have been proposed so far. These physical models can be largely grouped into the following three categories: elastic stress triggering, aseismic slip, and fluid flows. We also review several recent studies of foreshock sequences before moderate to large earthquakes around the world, focusing on how different results/conclusions can be made by different datasets/methods. Finally, we offer some suggestions on how to move forward on the research topic of earthquake nucleation and foreshock mechanisms and their governing factors.